Contribution to emotional regulation: The emergence of marital conflict in parents of children with special needs - Susanti Prasetyaningrum; Fifi Anggia; Eka Indah Nurmawati (University of Merdeka Malang, 2025)
Parents who have children with disabilities will face more difficult challenges in the parenting process. In raising children, both parents are equally responsible. The occurrence of conflict among parents who have children with special needs can cause differences in understanding of the child's needs. Parents need to have practical emotion regulation skills to manage conflict. This research aims to determine the influence of emotional regulation on marital conflict in parents of children with special needs. This research is quantitative research using accidental sampling techniques, and the research sample is 152 people, with the criteria being parents who have children with special needs aged 6 - 15 years. The scales used are The Emotion Regulation Questionnaire (ERQ) and the Kansas Marital Conflict Scale (KMCS). The research results obtained show that there is an influence of the emotional regulation variable on marital conflict in parents who have children with special needs (ABK) with a significance value (p) of 0.036 < 0.05. These results indicate that the higher an individual's emotional regulation ability, the lower the marital conflict.